2014
DOI: 10.1007/s12013-014-0048-8
|View full text |Cite
|
Sign up to set email alerts
|

Edaravone Protects Neurons in the Rat Substantia Nigra Against 6-Hydroxydopamine-Induced Oxidative Stress Damage

Abstract: To investigate the mechanism of the neuroprotective effect of edaravone in substantia nigra (SN) of the 6-OHDA-induced rat model of Parkinson's disease. Animal model of Parkinson's disease was induced in male Sprague-Dawley rats by injecting 6-OHDA into the left medial forebrain bundle. Subsequently, rats were intraperitoneally injected with 0.3, 1, or 3 mg/kg of edaravone for 14 days or with 3 mg/kg edaravone for 14 days followed by 14 days of no treatment. We evaluated the effect of edaravone on the rotation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…It is known that L-Dopa can also damage dopaminergic (DA) neurons (Blessing et al, 2003; Mena et al, 2009) as chronic treatment is associated with the development of complications such as dyskinesia, motor fluctuation, and dementia (Liu et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…It is known that L-Dopa can also damage dopaminergic (DA) neurons (Blessing et al, 2003; Mena et al, 2009) as chronic treatment is associated with the development of complications such as dyskinesia, motor fluctuation, and dementia (Liu et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Given the stable and reliable recording conditions provided by β-escin, we combined β-escin perforated patch clamp recordings with ratiometric fura-2 Ca 2+ imaging to analyze Ca 2+ handling properties. Using the added buffer approach, we determined the resting Ca 2+ concentration ([Ca 2+ ] i ), the Ca 2+ binding ratio κ S, and the extrusion rate γ of SN DA neurons, which display Ca 2+ dependent endogenous pacemaking properties (Liu et al, 2014; Neuhoff et al, 2002; Smits et al, 2013). Neurons were held at −70 mV to avoid spontaneous spiking.…”
Section: Resultsmentioning
confidence: 99%
“…Until now numerous studies have indicated the antioxidant, antiapoptotic, and anti‐inflammatory properties of EDA against toxic agents such as paraquat , 6‐hydroxydopamine , and rotenone . It has been reported that EDA could successfully preserve whole nigrostriatal dopaminergic systems against a 6‐hydroxydopamine‐induced rat model []. Another study demonstrated that a 5‐week treatment with EDA eliminated the toxic effects of rotenone on dopaminergic neurons by preventing ROS generation and mitochondrial damage .…”
Section: Discussionmentioning
confidence: 99%